2004
DOI: 10.1038/sj.tpj.6500280
|View full text |Cite
|
Sign up to set email alerts
|

Renin–angiotensin system gene polymorphisms: relationship with blood pressure and microalbuminuria in telmisartan-treated hypertensive patients

Abstract: This study analyzed the relationship between four renin-angiotensin system (RAS) gene polymorphisms and the response to blood pressure lowering and development of microalbuminuria in 206 patients with essential hypertension treated once daily for 12 months with telmisartan 80 mg. Seated cuff blood pressure and urinary albumin excretion (UAE) were measured throughout the study. Patients were screened for the presence of the A-6G variant of the angiotensinogen gene, angiotensin-converting enzyme insertion/deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 29 publications
2
23
0
6
Order By: Relevance
“…These endpoints have ranged from improvement in measured hemodynamics to reduction in proteinuria to BP response. However, significant conflicting data have since been reported that reveal no association between rs1799752 and ACEI or ARB BP response 17,[33][34][35][36][37][38][39] . Although evidence does not support the use of rs1799752 as a predictor of ACEI or ARB response, a few studies suggest this SNP may remain a predictor of diuretic response [40][41][42] .…”
Section: Candidate Pharmacodynamic Polymorphisms Of the Renin-angiotementioning
confidence: 99%
See 1 more Smart Citation
“…These endpoints have ranged from improvement in measured hemodynamics to reduction in proteinuria to BP response. However, significant conflicting data have since been reported that reveal no association between rs1799752 and ACEI or ARB BP response 17,[33][34][35][36][37][38][39] . Although evidence does not support the use of rs1799752 as a predictor of ACEI or ARB response, a few studies suggest this SNP may remain a predictor of diuretic response [40][41][42] .…”
Section: Candidate Pharmacodynamic Polymorphisms Of the Renin-angiotementioning
confidence: 99%
“…For variants in AGT, AT1, and AT2, most well-powered studies have failed to show consistent interactions between genotype and antihypertensive response 17,34,35 . In contrast, polymorphisms of REN have shown promise in Asian populations.…”
Section: Candidate Pharmacodynamic Polymorphisms Of the Renin-angiotementioning
confidence: 99%
“…Chaves et al (2001) found that the T573C polymorphism may be a genetic protective factor for urinary albumin excretion in a population of essential hypertensive patients. However, Redon et al (2005) found that neither blood pressure response nor the rate of urinary albumin excretion had any relationship with the presence of the T573C polymorphism while on telmisartan therapy. Our present results are consistent with the above findings.…”
Section: Discussionmentioning
confidence: 87%
“…Согласно доказательным данным телмисартан замедля-ет снижение СКФ, уменьшает микроальбуминурию у боль-ных с АГ [25], макропротеинурию у больных с мягкой и умеренной АГ [26]. Телмисартан превосходил гидрохлор-тиазид у пациентов с изолированной систолической АГ по влиянию на экскрецию альбумина с мочой, а при совмест-ном назначении телмисартана с лизиноприлом повышалась эффективность влияния на экскрецию альбумина с мочой у больных сахарным диабетом 2 [27].…”
Section: сахарный диабетunclassified